PENGARUH PARAMETER PENGELASAN TERHADAP HASIL UJI BENDING DENGAN STANDAR AWS PADA BAJA ASTM A36 - Veronika, Rika; Abdillah, Hamid; Hidayat, Ma’mun; Nainggolan, Irwan Kalam (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
In this modern era, technology is progressing rapidly, including welding techniques. In this welding process, a welder has a manual called WPS (Welding Procedure Specification). The role of WPS in welding is very important, this is because WPS is made to achieve good welding results and according to what is desired. Therefore, research regarding the suitability of WPS with welding results was carried out. This study uses an experimental method by performing GMAW (Gas Metal Arc Welding) welding in the 1G position and the test process is carried out with a bending test. This bending test process is carried out to find out whether the WPS used is in accordance with the desired results or not. In the bending test results that have been carried out by welding experiments twice, the bending test results are 3.528 kN/mm 2 . In this welding process, more optimal results were obtained using the amperage parameters of 94A – 106A and a voltage of 23 V – 25 V. In this process no visual welding defects were found so that this WPS could be used by trainees.